KLF2 controls the apoptosis of neutrophils and is associated with disease activity of systemic lupus erythematosus - Hongshuai Zhao; Zaichuan Lin; Peiwen Zhang; Jiayue Rao; Shumin Xu; Qing Luo; Junming Li (Arthritis Research & Therapy)
Abstract Background Neutropenia is more common in patients with systemic lupus erythematosus (SLE) and is a major cause of life-threatening infections. The increased apoptosis of neutrophils is likely to be an essential cause of neutropenia in SLE. However, the detailed mechanisms of increased neutrophil apoptosis in SLE remain unknown. This study focused on the role of Krüppel-like factor 2 (KLF2) in the regulation of neutrophil apoptosis and its association with SLE disease activity. Methods The levels of KLF2 in neutrophils from SLE patients and healthy controls (HCs) were detected by RT-PCR and western blot. The relationship between the levels of KLF2 and the apoptosis levels of neutrophils in SLE patients was analyzed. The KLF2 inhibitor Geranylgeranyl pyrophosphate (GGPP) and the KLF2 inducer geranylgeranyl transferase inhibitor (GGTI-298) were used to incubate with neutrophils to investigate the role of KLF2 in the regulation of neutrophil apoptosis. To clarify whether serum from SLE patients affects neutrophil KLF2 expression and apoptosis, sera from SLE patients were collected and used to incubate with neutrophils from HCs, followed by the detection of KLF2 levels and apoptosis levels of neutrophils. Additionally, the correlation between KLF2 levels and SLE disease activity index (SLEDAI) was analyzed. Results The expression of KLF2 in neutrophils of SLE patients was significantly suppressed, and the decreased KLF2 was associated with the upregulation of neutrophil apoptosis. Moreover, newly diagnosed SLE patients, SLE patients with higher serum IgG and positive anti-Smith antibodies had lower KLF2 expression. Furthermore, we demonstrated that modulating the expression of KLF2 can regulate the apoptosis of neutrophils. The levels of KLF2 in neutrophils were associated with the SLEDAI. In addition, we found that serum from SLE patients could induce apoptosis in neutrophils by down-regulating the expression of KLF2. Conclusions KLF2 controls the apoptosis of neutrophils and is associated with SLEDAI, which suggests that KLF2 in neutrophils may be involved in the occurrence and development of SLE.